A Longitudinal Analysis Reveals Early Activation and Late Alterations in B Cells During Primary HIV Infection in Mozambican Adults - Jiménez, Montse; Pastor, Lucía; Urrea, Victor; Rodríguez de la Concepción, María Luisa; Parker, Erica; Fuente-Soro, Laura; Jairoce, Chenjerai; Mandomando, Inacio; Carrillo, Jorge; Naniche, Denise; Blanco, Julià (Frontiers in Immunology, 2021)
Primary HIV infection (PHI) and subsequent chronic infection alter B cell compartment. However, longitudinal analysis defining the dynamics of B-cell alterations are still limited. We longitudinally studied B-cell subsets in individuals followed for one year after PHI (n=40). Treated and untreated chronic HIV infected (n=56) and HIV-uninfected individuals (n=58) were recruited as reference groups at the Manhiça District in Mozambique. B-cells were analyzed by multicolor flow-cytometry. Anti-HIV humoral response and plasma cytokines were assessed by ELISA or Luminex-based technology. A generalized activation of B cells induced by HIV occurs early after infection and is characterized by increases in Activated and Tissue-like memory cells, decreases in IgM-IgD- (switched) and IgM-only B cells. These alterations remain mostly stable until chronic infection and are reverted in part by ART. In contrast, other parameters followed particular dynamics: PD-1 expression in memory cells decreases progressively during the first year of infection, Transitional B cells expand at month 3-4 after infection and Marginal zone-like B cells show a late depletion. Plasmablasts expand 2 months after infection linked to plasma viral load and anti-p24 IgG3 responses. Most of well-defined changes induced by HIV in B-cell activation and memory subsets are readily observed after PHI, lasting until ART initiation. However, subsequent changes occur after sustained viral infection. These data indicate that HIV infection impacts B cells in several waves over time, and highlight that early treatment would result in beneficial effects on the B-cell compartment.